A Randomized Clinical Trial Of Lekhaniya Kashaya Vasti And Lekhaniya Ghan Vati In The Management Of Sthaulya (Obesity). - Antiwal, Meera; Singh, Jai Prakash (International Research Journal of Ayurveda & Yoga, 2021)
Background: Obesity is considering the world’s oldest metabolic disorder. It is not a single disease entity but a syndrome with many causes including mixture of genetic, nutritional and sociological factors. The World Health Organization considers obesity as “Insidious, creeping pandemic which is now engulfing the entire world”. There are eight body personality in Ayurveda, Sthaulya is one of them which deserves special attention. It is result of surfeit, when individual gorges on rich, sweet, cold fatty food, enjoys sleeping during day, refrains from mental work and suffers from genetic disorder. The patient with Sthaulya is continually ill and need to be managed. Therefore, diet and life style play a significant role both in development and control of obesity Sthaulya(obesity). In Ayurveda,Acharyas have mentioned about the use of Lekhaniya Vasti to manage the Sthaulya. Objective: To compare the efficacy of LekhaniyaKashayaVasti and Lekhniya GhanVati in patients of Sthaulya. Material and Methods:A total of 80 patients of Sthaulya were registered. Further they were divided into 2 groups each having 40 patients. In group I [LekhaniyaKashayaVasti] out of 40 patients 34 and in group II[LekhaniyaGhanVati] out of 40 patients 35 completed the follow up. Result: In Group I, mean change was observed in Body Mass Index (B.M.I.) [p<0.05]. Waist Hip Ratio (W.H.R.) [p<0.01], weight [p<0.001], Kshudraswas (Breathlessness) [p<0.001],and Nidraadhikya (Excessive sleep ) [p<0.001] which is statistically significant in comparisons with group II .